Nutrient cycling in integrated rangeland/cropland systems of the Sahel - Powell, J.M.; Fernández Rivera, S.; Hiernaux, Pierre H.Y.; Turner, M. (Society for Range Management, 1996)
The sustainability of nutrient transfers in integrated rangeland/cropland systems of the Sahel was examined in relation to the impact of livestock. Rangeland nutrient balances are considered in equilibrium whereas croplands lack the internal capacity to replenish nutrient off takes in grain and crop residues. Although soil nutrient removal is of general concern for the Sahel, local management practices of some farmers (e.g. corralling animals overnight on fields between cropping seasons, use of fertilizers, etc.) offset crop land nutrient removal. It is necessary to manage livestock so that they do not deplete the nutrient supply of rangelands in order to increase the manure supply for improving crop land productivity. It is considered that sustained rangeland productivity in the Sahel will depend greatly on producing alternative feeds derived mostly from crop lands and that land use and tenure policies that inhibit livestock mobility and, therefore, farmers access to the manure of pastoralist herds, will greatly undermine the resilience of the rangelands and increase the need for other external nutrient inputs such as fertilizers to prevent declines in soil fertility and crop yields.